The Descending Thoracic Aorta: Forgotten Vascular Access for Endovascular Device Delivery. Issue 2 (March 2016) - Allen, Keith B.; Borkon, A. Michael; Aggarwal, Sanjeev; Davis, J. Russell; Laster, Steven; Cohen, David J.; Chhatriwalla, Adnan K.; Hart, Anthony; Baron, Suzanne J.
Vascular access for large endovascular devices has evolved as patients have become more complicated and device indications have expanded. As the benefits of catheter-based treatments for aortic aneurysm repair and aortic valve replacement become mainstream, there is a need to address difficult vascular access by developing not only smaller-diameter devices but also creative options for vascular access. We describe direct descending thoracic aortic access during endovascular aneurysm repair, transcatheter aortic valve replacement, and redo mesenteric revascularization in three patients who did not have traditional access options.